Structural properties of yttrium iron garnet doped carbon black prepared via sol-gel technique - Mohammad Najmi, Mohammad Ali (2017)
There are several issues arise when using inorganic materials, for example, the procedure to generate literal substrate is complex because of many materials needed. It is also very expensive to run this product. Furthermore, the inorganic material is not environmental friendly and can lead to pollution and ecosystem imbalance. To overcome this issue, this agricultural waste such as sawdust can be set to be an important item as important as crude palm oil. Agriculture waste (sawdust) was controlled to be a carbon black by pyrolysis methods and have a good medium to be used as an electromagnetic wave absorber given the nature of the carbon material in maintaining the electromagnetic waves. Adding some rare earth elements and iron can increase the ability of the material to absorb electromagnetic waves. The main objective of this research are to prepare the waste carbon black by using pyrolisis technique and study the physical and structural properties of Yttrium Iron Garnet doped waste carbon black by using X-ray Diffratometry (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy (FESEM). The methodology of this study started with the preparation of waste carbon black by using pyrolysis technique. The sample will be mixed with the yttrium iron garnet with the ethanol absolute solution as the bonding agent for the sample. The finish sample then will undergoes characterization. Element of the sample has been analysis in the characterization of X-ray Diffratometry (XRD). Each of the graph of the sample show the present of Yttrium and Ferrite. For Fourier Transform Infrared Spectroscopy (FTIR), showed all powders presented O–H bond stretching from 3100 to 3600 cm−1, probably due to water absorption during test and the metal-oxygen vibrations at 577 cm−1 which are due to the lattice vibrational modes of the YIG unit cell. For FESEM, the surface and diameter of the particle are strongly depend on their molecular weight.